2017
DOI: 10.4236/ojfd.2017.73030
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Radiation-Convection Coupling of Greenhouse Using Underfloor Heating

Abstract: Greenhouse is an important place for crop growth, and it is necessary to control the temperature of growing environment in winter. In addition, the root temperature underground also plays a decisive role for plants growth. Adopting underground heating to increase the temperature can effectively improve the yield of crops. The objective of our study was to model the heat transfer of greenhouse underfloor heating which is analyzed and simplified based on the FLUENT software by changing the several important fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The CFD study has allowed the study of almost all existing passive greenhouse models worldwide, and has also been implemented as a tool for the optimization of climate management in greenhouses with active climate control [18][19][20]. There are currently a considerable number of studies applied to agricultural investors that have used CFD simulation to analyze thermal distribution [10,21,22], moisture distribution [5,21,23], efficiency of heating systems [24][25][26], the operation of cooling systems [27][28][29] and the microclimate generated as a function of different ventilation configurations [7,12,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The CFD study has allowed the study of almost all existing passive greenhouse models worldwide, and has also been implemented as a tool for the optimization of climate management in greenhouses with active climate control [18][19][20]. There are currently a considerable number of studies applied to agricultural investors that have used CFD simulation to analyze thermal distribution [10,21,22], moisture distribution [5,21,23], efficiency of heating systems [24][25][26], the operation of cooling systems [27][28][29] and the microclimate generated as a function of different ventilation configurations [7,12,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the maximum average temperature difference between the CFD simulation and measurement was 4.3°C. Jia et al [15] modeled the heat transfer of greenhouse underfloor heating system by the mean of the Fluent software. The effect of several important factors (pipe diameter, pipe spacing, laying depth, and supplied water temperature and flow rate) on the temperature distributions within the greenhouse system was evaluated.…”
Section: Introductionmentioning
confidence: 99%